(untitled) (Scientific journal of the Fergana State University, 2025)
The morphological variability of Schizothorax eurystomus, a native fish species of Uzbekistan’s water bodies, was investigated. Morphometric measurements of fish specimens collected from the Shohimardonsoy and Sokh rivers were analyzed using the Student’s t-test. Among the 29 examined traits, no significant differences were observed in 26, while the remaining 3 traits exhibited statistically significant differences at a 1% significance level. Additionally, the degree of morphological variability between populations was assessed using the coefficient of variation. The results indicated that in specimens from the Shohimardonsoy River, the length of the anal fin base and the interorbital distance showed low variability, whereas in the Sokh River specimens, these traits exhibited moderate variability. Furthermore, traits such as pectoral fin length, pelvic fin length, caudal peduncle length, and caudal peduncle depth displayed moderate variability in the Shohimardonsoy River population but low variability in the Sokh River population. Conversely, body depth and eye diameter, which demonstrated high variability in the Sokh River population, exhibited moderate variability in specimens from the Shohimardonsoy River.